(untitled) (Homoeopathy for All, 2026)
Background: The Organon of Medicine forms the philosophical and methodological foundation of homoeopathic practice, while the Homoeopathic Repertory functions as a practical instrument for remedy selection. Despite their intrinsic interdependence, both subjects are often taught and practiced in isolation, leading to mechanical repertorisation or philosophically weak prescriptions. Aim: To demonstrate the integration of Organon of Medicine with Homoeopathic Repertory through detailed clinical case analysis, illustrating the transition from aphorism-based reasoning to rubric based repertorial totality. Materials and Methods: An observational, case-based clinical study was conducted on patients attending routine homoeopathic OPD. Case taking, symptom evaluation, and individualization were guided by relevant aphorisms from the Organon of Medicine. Repertorial analysis was carried out using standard homoeopathic repertory, followed by individualized prescription and follow-up. Results: Aphorism-guided reperto rial analysis enabled meaningful rubric selection, accurate individu alization, and favorable clinical out comes in all cases presented. Conclusion: The Homoeopathic Repertory is a practical extension of the Organon of Medicine. An apho rism-to-rubric approach strengthens clinical reasoning, preserves philo sophical integrity, and enhances both teaching and practice of ho moeopathy.